Ação luterana e o associativismo religioso no tempo (1980 – 2000) - Berwaldt, Jean Carlos (2022)
This thesis is a research on religious associativism and its contribution to sustainable rural development. The objective was to analyze religious associativism based on bibliographic research, in interviews with Lutheran leaders from the most diverse instances of the IECLB and in experiences of Lutheran participation associations in two municipalities in the southern region of Brazil. This is a descriptive and exploratory study of a specific reality based on the analysis of the following sources: interviews with several pastors, secretaries of the IECLB; the AMPER Statute, as well as the minutes of its meetings; and documentary sources made available by the Evangelical Church of the Lutheran Confession in Brazil (IECLB). It should be noted that we did not identify the names of the two of us interviewees. The analysis of this quantitative documentation aimed to identify the cultural, socioeconomic and family profile of the two subjects involved in the research. This thesis, therefore, focuses on analyzing the problem of religious associativism and occurs through the IECLB, how it perceives and understands the relationship with sustainable development and how it perceives the issue of associativism over time. That is, how the understanding of the issue changes over time within the structures of the IECLB. Therefore, the first specific objective corresponds to the analysis of Lutheran thought, not respecting religious associativism and, as such, the thought contributes to sustainable development actions. A bibliographic review was carried out on the subject, highlighting religious associativism as one that works with assistance, philanthropic and community issues, important to develop a potential for emancipation and development of a community in the articulation of specific and comprehensive issues. The second objective corresponds to investigate the contributions of the Lutheran pastoral in the motivation and origin of the rural associations of small farmers in the experiences of AMPER and COOPEAGRI, as well as its implications for sustainable rural development. Our third objective is to make a comparative analysis of successes and failures between the experiences of rural associations of Lutheran origin with a view to sustainable rural development. I verify that, currently, despite AMPER and COOPEAGRI, we receive little support or two bodies from the IECLB, the second remains due to economic diversification and constant training/updating in associativism/cooperativism. Over the years, we have also identified that there is a lack of broad involvement of the Synod Ecclesiastical Leadership, or that this represents a symptom of the institution's lack of knowledge and responsibility for religious associativism and sustainable development. In this way, the institution becomes a resource analyst, no longer disregarding any commitment, as I assume two associative values, often becoming just a channel for the transmission of resources.